MEDIA PPT INTERAKTIF BERBASIS CANVA UNTUK PEMBELAJARAN SISTEM ORGAN TUBUH MANUSIA DI SEKOLAH DASAR - Wulandari, Novita; Ratno, Suyit; Hasibuan, Hanyfa Mardatilla; Manalu, Nola Br Boang; Marbun, Naomikha Glori; Andriyani, Nurul Aulia; Selvyanda, Selvyanda (Universitas Negeri Medan, 2026)
This study focuses on developing interactive PPT-based learning media using Canva for Natural and Social Sciences (IPAS) subjects, specifically the Human Body System material for fifth-grade elementary school students. In addition to producing media, this study also aims to assess the feasibility, practicality, and effectiveness of the media in improving learning outcomes. The development process follows the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation, resulting in a more systematic workflow. The assessment results from experts show that the developed media falls into the “highly feasible” category, with a score of 91.25% from subject matter experts and 90.8% from media experts. A small-scale field test also yielded positive responses, with teachers giving a rating of 94% and students 92.4%. These findings indicate that the media has a high level of practicality and is easy to use in learning. The effectiveness of the media is evident from the significant improvement in learning outcomes. The average pretest score of 52.1 increased to 86.4 on the posttest, with an N-gain score of 0.71, which is in the high category. The paired t-test results showed a significant difference between the scores before and after using the media, while the effect size of 3.6 indicated a very strong influence on student understanding. Overall, the Canva-based interactive PPT media proved to be able to strengthen concept understanding and improve